Neoadjuvant chemotherapy versus long-course neoadjuvant chemoradiotherapy for locally advanced rectal cancer: a systematic review and meta-analysis of 5,168 cases - Zhou, Wenjie; Wang, Xueting; Dan, Jie; Zhu, Minjie; Liao, Qian; Liu, Ke; Li, Jiangpeng; Jiang, Xianhong; Wang, Yonghong (Frontiers in Oncology, 2025)
BackgroundLong-course neoadjuvant chemoradiotherapy (Lc-NCRT) is the conventional treatment for locally advanced rectal cancer (LARC). It improves R0 resection rate and reduces local recurrence rate, but it cannot improve long-term oncological outcomes. It also causes several radiotherapy-related side effects. In recent years, some studies have shown that neoadjuvant chemotherapy (NCT) may be noninferior to Lc-NCRT. Therefore, we systematically evaluated the efficacy and safety of NCT and Lc-NCRT for LARC.MethodsCochrane Library, Embase, PubMed, WanFang Data, and CNKI were systematically searched as the relevant literature. The literature was screened independently by two groups, and data were extracted and evaluated for bias. A meta-analysis was performed using Revman5.4 software. The primary outcomes were tumor response to neoadjuvant therapy and long-term oncological outcomes.ResultsA total of 17 studies with 5,168 cases (1,957 cases in NCT and 3,211 cases in Lc-NCRT) were included in our meta-analysis. Compared with the Lc-NCRT group, although the NCT group had a lower pCR rate [RR = 0.65, 95% CI (0.56–0.75), P < 0.0001], less downstaging [RR = 1.11, 95%CI(1.03–1.19), P = 0.06] and more adverse events of neoadjuvant therapy [RR = 1.11, 95% CI (1.03–1.19); P = 0.06], it had no difference in long-term survival outcome [3-year overall survival: HR = 1.13, 95% CI (0.70–1.83), P = 0.62; 3-year disease-free survival: HR = 1.16, 95% CI (0.96–1.39), P = 0.12; 3-year local recurrence-free survival: HR = 1.36, 95% CI (0.9–2.08), P = 0.15] and serious adverse events [RR = 0.84, 95% CI (0.45–1.57), P = 0.58] from the Lc-NCRT group. Moreover, the incidence of anastomotic leakage [RR = 0.48, 95% CI (0.34–0.45)] and permanent stoma rate [RR = 0.7, 95% CI (0.58–0.84), P < 0.0001] after operation was lower in the NCT group.ConclusionNCT is a potential option for the treatment of LARC as it is beneficial for improving the sphincter preservation rate and reducing anastomotic leakage, the long-term oncological outcome is considerable, and the safety is controllable. Larger randomized controlled trials (RCT) with longer follow-up data are needed to clarify the specific regimens of NCT and the risk stratification of rectal cancer.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/home identifier, CRD42024579586.